Biomarkers reveal the terrigenous organic matter enrichment in the late Oligocene—early Miocene marine shales in the Ying-Qiong Basin, South China Sea - Ding, Wenjing; Li, Youchuan; Lei, Lan; Li, Li; Yang, Shuchun; Yang, Yongcai; Hou, Dujie (Acta oceanologica Sinica, 2023)
The increase of total organic carbon content of the late Oligocene—early Miocene terrigenously-dominated marine shales in the shallower depth intervals was reported in the Ying-Qiong Basin, South China Sea. The organic enriched lower Sanya Formation shales (early Miocene) have biomarker characteristics of tropical/subtropical plants, with abundant high molecular weight n-alkanes, angiosperm-derived oleanane, rearranged oleananes I, II, II, tricyclic/tetracyclic terpanes including des-A-oleanane, X, *, Y, Z, Z1 and bicadinanes W, T, T1, R. The biomarker characteristics are suggestive of larger influx of the dominant tropical/subtropical angiosperms in flora under a warming and more humid climate during depositions of the lower Sanya Formation (early Miocene) than the older Lingshui Formation (late Oligocene). The tropical/subtropical angiosperm input was thought as the prime control of terrigenous organic matter enrichment relative to the redox condition, and the coeval sea level changes and seafloor spreading in the South China Sea. Enrichment of the terrigenous organic matter in the early Miocene shales is likely in association with the coeval peak East Asian summer monsoon intensity in the South China Sea.